The Franz Boas Papers, Volume 2 : Franz Boas, James Teit, and Early Twentieth-Century Salish Ethnography - Boas, Franz, 1858-1942 (University of Nebraska Press, 2015)
"This inaugural volume of The Franz Boas Papers Documentary Edition series presents current scholarship from the various academic disciplines that were shaped and continue to be influenced by Franz Boas (1858-1942). Few of Boas's intellectual progeny span the range of his disciplinary and public engagements. In his later career, Boas moved beyond Native American studies to become a public intellectual and advocate for social justice, particularly with reference to racism against African Americans and Jews and discrimination against women in science. He was a passionate defender of academic freedom, rigorous scholarship, and anthropology as a humane calling. The Franz Boas Papers, Volume 1 examines Boas's stature as a public intellectual in three crucial dimensions: theory, ethnography, and activism. The volume's contributors move across many of the disciplines within which Boas himself worked, bringing to bear their expertise in Native studies, anthropology, history, linguistics, folklore, ethnomusicology, museum studies, comparative literature, English, film studies, philosophy, and journalism. This volume demonstrates a contemporary urgency to reassessing Boas both within the field of anthropology and beyond."-- Provided by publisher.
Volume 1 is the product of a conference held in December 2010 at the University of Western Ontario.
"In partnership with the American Philosophical Society (APS) and the University of Nebraska Press, this volume initiates an ambitious project to digitize and critically edit the Franz Boas papers. We anticipate approximately twenty-five volumes ..."--Volume 1, page 345.
Volume 1. Franz Boas as public intellectual : theory, ethnography, activism / edited by Regna Darnell, Michelle Hamilton, Robert L.A. Hancock, and Joshua Smith.
Keywords: Boas, Franz, -- 1858-1942 -- Influence.; Boas, Franz, -- 1858-1942 -- Notebooks, sketchbooks, etc.; Boas, Franz, -- 1858-1942 -- Diaries.; Boas, Franz, -- 1858-1942 -- Correspondence.; Boas, Franz, -- 1858-1942; Boas, Franz -- 1858-1942; Ethnology -- North America -- History.; Ethnologie -- Amérique du Nord -- Histoire.; SOCIAL SCIENCE -- Anthropology -- General.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; BIOGRAPHY & AUTOBIOGRAPHY / Historical; Influence (Literary, artistic, etc.); Ethnology; North America; Wissenschaft; Rezeption; Theorie; Aktivismus; Ethnologie; Personal correspondence; Notebooks, sketchbooks, etc.; History; Diaries